A comparison of velocity measurements from the CUTLASS Finland radar and the EISCAT UHF system - J. A. Davies; M. Lester; S. E. Milan; T. K. Yeoman (Annales Geophysicae, 1999)
The CUTLASS Finland radar, which comprises an integral part of the SuperDARN system of HF coherent radars, provides near continuous observations of high-latitude plasma irregularities within a field-of-view which extends over some four million square kilometres. Within the Finland radar field-of-view lie both the EISCAT mainland and EISCAT Svalbard incoherent scatter radar facilities. Since the CUTLASS Finland radar commenced operation, in February 1995, the mainland EISCAT UHF radar has been run in common programme 1 and 2 modes for a total duration exceeding 1000 h. Simultaneous and spatially coincident returns from these two radars over this period provide the basis for a comparison of irregularity drift velocity and F-region ion velocity. Initial comparison is limited to velocities from four intervals of simultaneous radar returns; intervals are selected such that they exhibit a variety of velocity signatures including that characteristic of the convection reversal and a rapidly fluctuating velocity feature. Subsequent comparison is on a statistical basis. The velocities measured by the two systems demonstrate reasonable correspondence over the velocity regime encountered during the simultaneous occurrence of coherent and incoherent scatter; differences between the EISCAT UHF measurements of F-region ion drift and the irregularity drift velocities from the Finland radar are explained in terms of a number of contributing factors including contamination of the latter by E-region echoes, a factor which is investigated further, and the potentially deleterious effect of discrepant volume and time sampling intervals. Key words. Ionosphere (ionospheric irregularities; plasma convection)